Evaluasi Kesehatan dan Keselamatan Kerja dengan Metode HIRARC pada PT. Charoen Pokphand Indonesia - Wijaya, Albert; Panjaitan, Togar W.S; Palit, Herry Christian (Jurnal Titra, 2015)
PT. Charoen Pokphand Indonesia is a fodder company which is located in Surabaya â Mojokerto Street 26 Km, Krian City. This company consists of 4 areas which are feed mill area, raw material area, silo area, and finished good area. The company was in the preparatory stage SMK3 certification .Companies now want to evaluate the system of K3 with HIRARC that is one of the documents supporting SMK3 certification certification. If the company applies HIRARC, the dangerous activities in the company can be detected and the solution can be made immediately. As a result, the number of the accident in the workplace can be minimized. HIRARC method consists of 3 things which are hazard identification, risk assessment, and risk control. The data which is processed with HIRARC is got from the interview, observation, and companyâs data. The result of health and safety evaluation with HIRARC method through PT Charoen Pokphand Indonesia is that there are still many dangerous activities; for example, an activity which has extremely high, high, and normal percentage of risk rating. The percentages of the dangerous activities in silo area are 8,82% in extremely high rate, 14,71% in high rate, and 47,06% in normal rate. On the other hand, the percentage of the dangerous activities in raw material warehouse are 14% in extremely high rate, 35% in high rate and 39% in normal rate. Those dangerous activities must be solved immediately by making risk control. The risk control which is suggested are giving sanctions, making checklist, maintaining the tools, replacing the tools if they are broken, changing the method, and giving training. The potential percentage of the dangerous activities which is expected to decrease in silo area is disappearing the extremely high risk, decreasing the percentage of the high and normal risk to 8,82%, and 23,53%. On the other hand, the potential percentage of dangerous activities which is expected to decrease in raw material warehouse is disappearing the extremely high risk, decreasing the percentage of high and normal risk to15,79% and 21,05%.